Detection, occurrence, and fate of emerging contaminants in agricultural environments (2020). (29th August 2020) - Snow, Daniel D.; Cassada, David A.; Biswas, Saptashati; Malakar, Arindam; D'Alessio, Matteo; Marshall, Alice H. L.; Sallach, Jonathan B.
Abstract: A review of 79 papers published in 2019 is presented. The topics ranged from detailed descriptions of analytical methods, to fate and occurrence studies, to ecological effects and sampling techniques for a wide variety of emerging contaminants likely to occur in agricultural environments. New methods and studies on veterinary pharmaceuticals, antibiotics, anthelmintics, and engineered nanomaterials in agricultural environments continue to expand our knowledge base on the occurrence and potential impacts of these compounds. This review is divided into the following sections: Introduction, Analytical Methods, Antibiotics in Agroecosystems, Pharmaceutical Fate and Occurrence, Anthelmintics and Engineered Nanomaterials. Practitioner points: New research describes innovative new techniques for emerging contaminant detection in agricultural settings Newer classes of contaminants include human and veterinary pharmaceuticals Research in nanomaterials show that these also occur in agricultural environments and will likely be topics of future work